Deep Eutectic Solvent (DES) Based on Choline Chloride and Mono-, Di-, Poly-Ethylene Glycol as KI/I2 Electrolyte Solvents on DSSC Devices - Adhitya Adhitya; Winda Rahmalia; Intan Syahbanu; Gusrizal Gusrizal; Adhitiyawarman Adhitiyawarman (Universitas Gadjah Mada, 2023)
Deep eutectic solvent (DES) has high viscosity and electrical conductivity values, so it can be used as an electrolyte solvent in dye-sensitized solar cells (DSSCs). This research was conducted to produce DES based on choline chloride (ChCl) and ethylene glycol (EG), diethylene glycol, and polyethylene glycol-400, which were then used as KI/I2 couple redox electrolyte solvent to improve the DSSC performance. The synthesis was carried out by mixing each component in several variations of the mole fraction of ChCl (xCHCl) at 80 °C for 15 min, and then was characterized by their pH, freezing point, density, viscosity, and electrical conductivity. A mixture that meets the criteria as a eutectic solvent and has a freezing point of less than −18 °C with the highest electrical conductivity value is DES ChCl:EG with xChCl 0.3 and xChCl 0.4. Both DESs were then used as a solvent for KI/I2, combined with acetonitrile in various compositions. The electrolyte with the highest electrical conductivity value was KI/I2 dissolved in ChCl:EG with xChCl 0.3 solvent 6:4 v/v, and then employed in DSSC device. The best performance of DSSC (Isc= 0.155 mA/cm2; Voc=0.465 V; Pmax= 0.719 W; ηmax= 0.072%) was produced under a light intensity of 0.1 W/cm2.